Complex Management of Labial Synechiae with Chronic Grade 4 Perineal Rupture: A Rare Case and Surgical Insight - Setiawati, Dewi; Irianta, Trika; Idrus, Hasta Handayani (Journal of Neonatal Surgery, 2025)
Background: Labial synechiae, characterized by the partial or complete adhesion of the labia, is a rare condition in adult women. This condition may arise secondary to trauma, infections, or post-surgical scarring. The case becomes more complex when accompanied by a history of obstetric trauma, such as a Grade 4 perineal rupture, which involves injury to both the anal sphincter and rectal mucosa. Early identification and appropriate management are crucial to prevent complications like chronic pain, dyspareunia, and urinary or fecal incontinence. Case Presentation: We report the case of a 27-year-old multiparous woman presenting with extensive labial synechiae and a history of Grade 4 perineal rupture sustained during childbirth five years prior. She complained of recurrent genital discomfort, dyspareunia, and difficulty with urination. Physical examination revealed complete fusion of the labia minora and extensive scarring around the perineal and anal regions. Imaging studies confirmed the presence of post-traumatic adhesions without fistula formation. Results: The patient underwent a successful surgical intervention involving labial adhesion release and perineal reconstruction. Postoperatively, the patient demonstrated marked improvement in genital and urinary function, and her dyspareunia resolved entirely. Follow-up at six months revealed no recurrence of adhesions, and the patient reported a significant enhancement in her quality of life. Conclusion: This case highlights the importance of recognizing and managing labial synechiae in adult women, particularly when compounded by severe obstetric trauma. Surgical intervention, combined with appropriate postoperative care, can yield excellent functional and psychological outcomes.